PENGARUH GREEN SUPPLY CHAIN MANAGEMENT TERHADAP ENVIRONMENTAL PERFORMANCE PADA UKM INDUSTRI PENGOLAHAN DI JAWA TIMUR - Indah Ayu Lestari Kasim; Erna Andajani; Fitri Novika Widjaja (Perpustakaan Universitas Surabaya, 2024)
Abstract—This research was conducted with the aim of examining the influence of green supply chain management on environmental performance in processing industry SMEs in East Java. The type of research used is quantitative research with an interval level of 1 to 5. Data taken was 260 respondents from online distribution. The data obtained was then used to test existing hypotheses using SPSS (Package for Social Sciences) with software, namely SPSS 20, to test validity and reliability. Then to test the research model using PLS-SEM (Partial Least Squares-Structural Equation) with Smart-PLS 3.0 software. The research results state that strategic orientation (SO) has a significant positive effect on green supply chain management (GSCM), internal environment management (IEM) has a significant positive effect on green supply chain management (GSCM), green supply chain management (GSCM) has a significant positive effect on environmental performance (EP), government regulation (GR) has a significant positive effect on green supply chain management (GSCM), strategic orientation (SO) has no effect on environmental performance (EP) through green supply chain management (GSCM), internal environment management (IEM ) has a significant positive effect on environmental performance (EP) through green supply chain management (GSCM), and government regulation (GR) has a significant positive effect on environmental performance (EP) through green supply chain management (GSCM. Keywords: environmental performance, green supply chain management, internal environment management Abstrak—Penelitian ini dilakukan bertujuan untuk menguji Pengaruh Green Supply Chain Management Terhadap Environmental Performance pada UKM Industri Pengolahan Di Jawa Timur. Jenis penelitian yang digunakan adalah penelitian kuantitatif dengan aras interval 1 sampai dengan 5. Data yang diambil sebanyak 260 responden dari penyebaran online. Data yang didapat kemudian digunakan untuk menguji hipotesis yang ada menggunakan SPSS (Package for Social Sciences) dengan software yaitu SPSS 20 untuk uji validitas dan reliabilitas. Kemudian untuk menguji model penelitian menggunakan PLS-SEM (Partial Least squares-Structural Equation) dengan software Smart-PLS 3.0. Hasil penelitian menyatakan bahwa strategic orientation (SO) berpengaruh signifikan positif terhadap green supply chain management (GSCM), internal environment management (IEM) berpengaruh signifikan positif terhadap green supply chain management (GSCM), green supply chain management (GSCM) berpengaruh signifikan positif terhadap environmental performance (EP), government regulation (GR) berpengaruh signifikan positif terhadap green supply chain management (GSCM), strategic orientation (SO) tidak berpengaruh terhadap environmental performance (EP) melalui green supply chain management (GSCM), internal environment management (IEM) berpengaruh signifikan positif terhadap environmental performance (EP) melalui green supply chain management (GSCM), dan government regulation (GR) berpengaruh signifikan positif terhadap environmental performance (EP) melalui green supply chain management (GSCM). Kata kunci: environmental performance, green supply chain management, internal environment management